Arbovirus studies ofbats from Zulia state: Serological survey for Venezuelan, eastern and western Encephalitis virus antibodies. February 1976 - Dickerman, Robert; Ryder, Slavia; Martín, Mary (Investigación Clínica, 2013)
One hundred and forty five bats of 13 specles collected during February 1976 at three sites in the State of Zulia. Venezuela, were negative for hemagglutination-inhibition [HI) and neutralization antibodies to Venezuelan encephalitis virus. One hundred and thirty seven of these were also negative for HI antibodies to both Eastern and Western encephalitis viruses. Due to small series for most species in the sample, negative results are difficult to interpreto